The Brazilian World Cup: too hot for soccer? - Luna, R.; Torres Steinke, E.; Pacheco, C.; Lima Vieira, L.; Olaya Betancour, M.; Steinke, V. A. (International Journal of Biometeorology, 2017)
The main objective of this research was to analyze the climate data for the host cities of the soccer World Cup held in Brazil in June and July 2014. A great deal of criticism was expressed about the Brazilian climate in the national and international press and media in the run-up to the competition, suggesting that the air temperature and relative air humidity would be the main adversaries of the soccer teams, especially those from Europe, during the competition. An analysis of the weather was done at the places and times of each of the 64 matches held. A human thermal comfort index was calculated (discomfort index (DI)) for each of the matches in order to discover the real climatic conditions in the host cities during the 2014 World Cup and their potential influence on the teams and human comfort in general. During the 2014 World Cup, only two matches were played at temperatures above 30 °C, representing a negligible percentage of the total number of matches. The air temperature for over half the matches (53%) was 20-25 °C. The results showed the air temperature and relative humidity data analyzed here both individually and in the form of an index indicate that the World Cup held in Brazil in 2014 did not put any of the players at risk due to extreme heat.